Navigating the contours of maritime defence cooperation between India and Japan: Impulses, challenges and opportunities. (2nd July 2020) - Chakraborty, Mohor
ABSTRACT: Maritime affairs have been experiencing a state of flux in the Indo-Pacific region, particularly since the beginning of the present decade, attributable to the policies of an assertive China, consequently evoking proportional responses from regional state actors. Amid this transforming scenario, regional states such as India, Japan and Australia have devised policies towards ensuring uninterrupted freedom of navigation and overflight of the Indo-Pacific waterways, given their strategic and commercial sensitivity as sea lanes of communication. The compulsion of sustaining the maritime balance of power in the Indo-Pacific region has necessitated responsible states like India and Japan to forge and bolster bilateral defence cooperation, in keeping with their respective national interests, policies and guidelines. Against this backdrop, this article analyses the impulses, dynamics and challenges of maritime cooperation between India and Japan, particularly in the defence-industrial realm. It underscores the imperative of sustaining and further strengthening the dynamics of bilateral defence-industrial cooperation and optimally exploring the opportunities unveiled by policies like "Make in India", in sync with Japan's quest for defence modernisation and development, towards securing a free and open Indo-Pacific.